Strengthening regional capacity for climate services in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Key institutions working on climate services in Africa have embarked on a collective process towards strengthening and scaling up climate information and advisory services for agriculture in Africa. Researchers and technical experts, from these institutions, met during a pre event to the fifth conference on Climate Change and Development in Africa (CCDA-V) in Victoria Falls, Zimbabwe held between 28 - 30 October 2015. Discussions were an important step toward a collaborative effort to strengthen capacity, through African regional institutions, to support smallholder farmers with relevant climate services. Find out about the meeting outputs: coordinating climate services with key institutions in Africa.